Accumulation of dry matter and nutrients by corn grown under doses of formulated mineral and organomineral npk (Research, Society and Development, 2021)
Knowledge of the extraction and accumulation of nutrients by plants during their development helps to determine their nutritional needs and is relevant to improve the recommendation for mineral and organomineral fertilizers. The objective of this study was to evaluate the effect of doses of sources of formulated mineral and organomineral NPK on the dry matter productivity of the aerial part and on the accumulation of macronutrients and micronutrients by corn. The experiment was carried out in plastic pots, arranged in the open, filled with 25 L of soil, collected from a dystrophic Red Latosol, closed phase, at the Experimental Farm of the Federal Goiano Institute, Rio Verde Campus - GO. The experimental design used was randomized blocks, in a 5x2 factorial scheme, with four replications. The treatments were five doses of formulated NPK 04-14-08 (0, 150, 300, 450, 600 kg ha-1 of the product, equivalent to pot) and two sources of fertilizers: mineral and organomineral formulation, 04-14-08. The corn plants were harvested at 75 days after sowing, with the cut of the stalk close to the soil. In the plants, evaluations of dry mass productivity of the aerial part and accumulation of macronutrients (N, P, K, Ca, Mg and S) and micronutrients (Cu, Fe, Mn and Zn) were carried out. The organomineral source provided higher dry matter productivity to corn. The accumulation of nutrients followed the decreasing order N> K> Mg> Ca> S> P> Fe> Mn> Zn> Cu. The organomineral source, in the same doses as the mineral formulation, has the potential to replace mineral sources.